Synthesis, analysis of single crystal structure and computational studies on a novel picrate derivative: 2-(Pyridine-2-ylthio)pyridine-1-ium picrate - Aydin, Fatma; Kiraz, Asli Ozturk (European Journal of Chemistry, 2025)
A new organic salt, 2-(pyridine-2-ylthio)pyridine-1-ium picrate (C16H11N5O7S: 2-PyrTPPc), has been synthesized and characterized using various spectroscopic methods such as 1H NMR, 13C NMR, and FT-IR. The crystal structure of the title compound was analyzed using X-ray structure analysis, which revealed that it belongs to the monoclinic P21/c space group with a = 16.876(4) Å, b = 7.6675(18) Å, c = 13.846(3) Å, Z = 4, and V = 1766.9(7) Å3. The molecular packing of the compound showed the presence of several intermolecular hydrogen bonds between different atoms. The electronic properties of the crystal were investigated using density functional theory (DFT) with B3LYP/6-311G(d,p) level. Frontier molecular orbitals were drawn and related global quantities such as electronic chemical potential, chemical hardness-softness, electrophilicity, HOMO and LUMO energy eigenvalues, and the difference between HOMO and LUMO (∆E) were calculated and discussed. TG/DTG analysis revealed the thermal stability of the 2-PyrTPPc crystal. The single stage of decomposition and the sharpness of the peak in the temperature range of 157-224 °C illustrated the purity and good crystallinity of the grown crystal. The different vibration modes of the 2-PyrTPPc molecule were determined by analyzing the FT-IR and FT-Raman spectra. The detection of vibrations of the pyrNH+ and aromatic thioether moiety supports the confirmation of the di(pyridin-2-yl)sulfane structure through the intermediate formed by the transfer of the proton from picric acid to 2-mercaptopyridine.